Sturge-Weber syndrome and glaucoma - Sambavi Anbuselvan; Paneerselvam Venkatachalam (Wolters Kluwer Medknow Publications, 2021)
Sturge-Weber syndrome (SWS) is a neurocutaneous syndrome characterized by capillary venous malformations in the skin, eye, and brain with the occurrence of angiomas of the face, choroid, and leptomeninges. The characteristics signs include facial port-wine birth mark, glaucoma, choroidal hemangioma with brain malformations, and cognitive abnormalities. In this article, we have documented the case report of a 24-year-old male with SWS presenting with glaucoma.